2005
DOI: 10.3171/spi.2005.3.4.0262
|View full text |Cite
|
Sign up to set email alerts
|

Spinal stenosis due to ossified lumbar lesions

Abstract: Object. Spinal stenosis due to lumbar ossified lesions is a rare pathological entity. The authors retrospectively evaluated the clinical features and surgical results associated with cases involving lumbar ossified lesion—induced stenosis. Methods. Data obtained in 20 surgically treated patients with lumbar hyperostotic spinal stenosis were included. To evaluate the background of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 31 publications
0
15
0
4
Order By: Relevance
“…Some reports have shown correlations between preoperative mJOA scores or the duration of a preoperative symptom with postoperative outcomes [10]. In many studies, the classification for configuration of OLF failed to show any significance as a prognostic factor [8,10,14,15,22,23]. In our series, the classification of axial configuration into fused or non-fused types demonstrated a significant correlation to patient outcome.…”
Section: Discussionmentioning
confidence: 38%
“…Some reports have shown correlations between preoperative mJOA scores or the duration of a preoperative symptom with postoperative outcomes [10]. In many studies, the classification for configuration of OLF failed to show any significance as a prognostic factor [8,10,14,15,22,23]. In our series, the classification of axial configuration into fused or non-fused types demonstrated a significant correlation to patient outcome.…”
Section: Discussionmentioning
confidence: 38%
“…In contrast, Chang et al [13] reported that the coexistence of thoracic OLF and other spinal disorders was related to poor outcome. Similarly, in the case of spinal stenosis due to ossiWed lumbar lesion, coexisting spinal lesions including thoracic OLF were associated with a poorer surgery related outcome [14]. A caveat of those studies was that they used heterogeneous cohorts with regard to several clinical factors, including the duration of the disease process before decompression, which appeared to have prognostic value in thoracic OLF [3,15,16].…”
Section: Discussionmentioning
confidence: 97%
“…On axial CT scans, the mean mass occupying ratio was 38.7% (range 16%-74.5%). The mean score on the mJOAS, as a reflection of clinical status, was 14.3 (range [8][9][10][11][12][13][14][15][16][17][18]. Figure 1 shows the average mJOAS score for each comorbid and radiographic condition.…”
Section: Cervical Opllmentioning
confidence: 99%
“…Cervical and thoracic OPLL typically manifests with signs and symptoms of myelopathy, while the lumbar disease usually manifests with signs and symptoms of stenosis. 17,27,29 Predictors and risk factors for the development or progression of myelopathy include > 60% OPLL-induced spinal stenosis, increased range of motion of the cervical spine, progression of OPLL, type of OPLL (that is, the segmental type is associated with the greatest risk), and lateral-deviated OPLL. [25][26][27]30 After 30 years, however, myelopathy-free rates as high as 71% have been reported among patients who had no myelopathy when the OPLL was first diagnosed.…”
mentioning
confidence: 99%